1996
DOI: 10.3758/bf03331961
|View full text |Cite
|
Sign up to set email alerts
|

Escapable stress modulates retention of spatial learning in rats: Preliminary evidence for involvement of neurosteroids

Abstract: The ability to escape stress has been shown to protect an organism from many of the deleterious effects of stress exposure. It has been suggested that this amelioration could be mediated by the release of an endogenous benzodiazepine-like substance in the brain demonstrated 2 h poststress. Since benzodiazepines possess amnestic as well as antianxiety actions, the possibility of memory alterations in coping subjects was evaluated. Animals were randomly assigned to three groups: escapable shock, yoked inescapabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 60 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…For example, we have found that stressors such as inescapable shock induce IL-1 in the hippocampus as well as in the hypothalamus. It is thus interesting to note that stressors have been reported to interfere with both LTP in the hippocampus (Shors, Siet, Levine, & Thompson, 1989) and the memory for spatial learning (Healy & Drugan, 1996). It is not known whether brain IL-1 is, in fact, responsible for these.…”
Section: Cognitionmentioning
confidence: 99%
“…For example, we have found that stressors such as inescapable shock induce IL-1 in the hippocampus as well as in the hypothalamus. It is thus interesting to note that stressors have been reported to interfere with both LTP in the hippocampus (Shors, Siet, Levine, & Thompson, 1989) and the memory for spatial learning (Healy & Drugan, 1996). It is not known whether brain IL-1 is, in fact, responsible for these.…”
Section: Cognitionmentioning
confidence: 99%